Budidaya Maggot Lalat Black Soldier Flies (BSF) sebagai Pakan Ternak - Salman Salman; Lalu Muhammad Ukhrawi; Muhammad Azim (Universitas Mataram, 2020)
Waste management in some areas is still a problem for the environment. One method to manage the waste is by using it as a medium for maggot cultivation BSF (Black Soldier Flies) flies. Therefore, a KKN team, from Mataram pioneered the BSF fly maggot cultivation business in Pendem Village, Janapria District, Central Lombok Regency, West Nusa Tenggara. The purpose of this program is to empower Pendem Village residents to process organic waste through cultivation of BSF maggot flies into animal feed. The method was by conducting counseling or socialization with village staff in front of local community leaders and directly making BSF cage. The results shown a positive response from residents. Besides that, the team produced the animal feed from this cultivation. and also, the organic fertilizer in the form of packaging ready for market.